On Boundaries - Cabrera-Febola, Walter (2014)
The exchange of information between natural entities is made through boundaries, this begs for a systematic study of them which so far has been lacking. Here, such study is provided, thus it begins by establishing a general conceptualization of boundary, which has been stated in a previous paper by the author, followed by the identification of some kind of boundaries. Thus, interface, limit, border and some of its kinds, and barrier are identified and conceptualized. Then, a partial study of some of the conceptualized boundaries is provided trying to analyze them as much as possible. Finally, a general discussion on the existence and importance of boundaries is given remarking the generality and robustness of the concept of boundary and its different kinds, hence its utility in science and technology is appreciated.